Sugarcane responses to two strains of Xanthomonas albilineans differing in pathogenicity through a differential modulation of salicylic acid and reactive oxygen species - Zhao, Jian-Ying; Chen, Juan; Shi, Yang; Fu, Hua-Ying; Huang, Mei-Ting; Rott, Philippe C.; Gao, San-Ji (Frontiers in Plant Science, 2022)
Leaf scald caused by Xanthomonas albilineans is one of the major bacterial diseases of sugarcane that threaten the sugar industry worldwide. Pathogenic divergence among strains of X. albilineans and interactions with the sugarcane host remain largely unexplored. In this study, 40 strains of X. albilineans from China were distributed into three distinct evolutionary groups based on multilocus sequence analysis and simple sequence repeats loci markers. In pathogenicity assays, the 40 strains of X. albilineans from China were divided into three pathogenicity groups (low, medium, and high). Twenty-four hours post inoculation (hpi) of leaf scald susceptible variety GT58, leaf populations of X. albilineans strain XaCN51 (high pathogenicity group) determined by qPCR were 3-fold higher than those of strain XaCN24 (low pathogenicity group). Inoculated sugarcane plants modulated the reactive oxygen species (ROS) homoeostasis by enhancing respiratory burst oxidase homolog (ScRBOH) expression and superoxide dismutase (SOD) activity and by decreasing catalase (CAT) activity, especially after infection by X. albilineans XaCN51. Furthermore, at 24 hpi, plants infected with XaCN51 maintained a lower content of endogenous salicylic acid (SA) and a lower expression level of SA-mediated genes (ScNPR3, ScTGA4, ScPR1, and ScPR5) as compared to plants infected with XaCN24. Altogether, these data revealed that the ROS production-scavenging system and activation of the SA pathway were involved in the sugarcane defense response to an attack by X. albilineans.